IMPROVING THE SILAGE QUALITY OF NAPIER GRASS (PENISSETUM PUPUREUM) USING PROBIOTIC LOCAL MICROORGANISM (MOL) BANANA STEM (MUSA PARADISIACA) - Raihan, M.; Yustendi, Dedhi; Mulyadi, Mulyadi; Haryadi, Haryadi (International Journal Multidisciplinary (IJMI), 2025)
Objective: This study aims to determine the improvement of the quality of napier grass silage (pennisetum purpureum) by using Probiotic Local Miroorganism (MOL) banana stems on moisture content, ash content, protein, fat and crude fiber. Method: This research was conducted at the Faculty of Agriculture Laboratory, Abulyatama University, Aceh Besar Regency. This study used a completely randomised design (CRD) one-way pattern with 4 treatments and 4 replications. The treatments consisted of P0 (Napier grass without mole (control)), P1 (Napier grass treated with mole with a concentration of 1 ml), P2 (Napier grass treated with mole with a concentration of 2 ml) and P3 (Napier grass treated with mole with a concentration of 3 ml). Results: The results showed that the addition of 2 ml MOL in napier grass silage could reduce the water content to 67.08%, while the protein content increased to 12.43% with the addition of 3 ml MOL. The addition of probiotics in napier grass silage had a very significant effect (P<0.01) on crude fiber, protein and moisture content. While the addition of MOL in silage had no significant effect (P>0.05) on fat content and ash content. Novelty: This research demonstrates an innovation in improving the quality of elephant grass silage by utilizing local probiotic microorganisms (ML) from banana stems, a previously unused approach. The novelty lies in the use of MOL from banana stems as a silage fermentation additive, which has been shown to significantly increase protein content and reduce moisture content, as well as positively impact crude fiber.